Pengembangan Bahan Ajar Matematika Materi Keliling Dan Luas Bangun Datar Menggunakan Kalkulator Kelas IV SD - Candra Khaulatin Dewi; Sony Irianto; Ana Andriani (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2020)
This research is motivated by the absence of teaching materials for learning mathematics and to dispel the myth that a calculator can make students stupid. The results of this study are in the form of a traveling material book and wide flat area used for teachers and students in the learning process. This study aims to determine the feasibility of mathematics teaching material products. This research is a research and development of Borg and Gall, namely: (1) Potential and problems; (2) Data / Information Collection; (3) Product Design; (4) Design validation; (5) Design improvements; (6) product trials. Validation was carried out by 3 experts namely teaching material experts, material experts and linguists, the test subjects were 29 elementary students of UMP. The results of the assessment of teaching experts, material experts and linguists show 4.5 in the category of "Valid / worthy". The results of the responses of students viewed from the percentage of students in the initial field trials by 29 students in SD UMP showed 4.23, with the category "good". From the results of the validation of experts, practitioners and the students' responses the researchers concluded that the products of the Central Javanese traditional game model were appropriate for use in learning mathematics and could dispel the myths of using calculators that made students stupid.